Assessing the potential of environmental DNA metabarcoding for monitoring Neotropical mammals: a case study in the Amazon and Atlantic Forest, Brazil - Sales, Naiara Guimarães; Kaizer, Mariane da Cruz; Coscia, Ilaria; Perkins, Joseph C.; Highlands, Andrew; Boubli, Jean Philippe; Magnusson, William Ernest; Silva, Maria Nazareth Ferreira da; Benvenuto, Chiara; McDevitt, Allan D. (Mammal Review, 2020)
The application of environmental DNA (eDNA) metabarcoding as a biomonitoring tool has greatly increased, but studies have focused on temperate aquatic macro-organisms. We apply eDNA metabarcoding to detecting the mammalian community in two high-biodiversity regions of Brazil: the Amazon and Atlantic Forests. We identified Critically Endangered and Endangered mammalian species and found overlap with species identified via camera trapping. We highlight the potential for using eDNA monitoring for mammals in biodiverse regions and identify challenges: we need a better understanding of the ecology of eDNA within variable environments and more appropriate reference sequences for species identification in these anthropogenically impacted biomes. © 2020 The Mammal Society and John Wiley & Sons Ltd